2022
DOI: 10.47391/jpma.aku-22
|View full text |Cite
|
Sign up to set email alerts
|

Radial artery coronary bypass grafting: Surgical outcomes of an unexplored innovation in a developing country

Abstract: Objective: To explore postoperative outcomes, particularly prolonged length of hospital stay, in radial arterycoronary artery bypass graft patients in a tertiary-care setting.Methods: The pilot prospective cohort study was conducted at the Aga Khan University Hospital, Karachi, fromSeptember 2019 to September 2020, and comprised adult patients of either gender due to undergo coronary arterybypass grafting for coronary artery disease involving two or more vessels. The subjects approached for the use oftheir rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our findings were similar with the previous studies which demonstrated mean length of hospital stay as 8.10±2.37 days in conventional CABG group and higher age as significant predictor of prolonged hospital stay (p<0.05). 6,[16][17][18][19] A study by Parasca,C. A et al, found mean aortic cross-clamp time and CPB time to be higher in arterial group when compared with venous group (62.3±24.6mins, 92.7±31.7mins vs 55.9±35.7, 87.8±35.9) respectively due to technically demanding anastomosis with arterial grafts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings were similar with the previous studies which demonstrated mean length of hospital stay as 8.10±2.37 days in conventional CABG group and higher age as significant predictor of prolonged hospital stay (p<0.05). 6,[16][17][18][19] A study by Parasca,C. A et al, found mean aortic cross-clamp time and CPB time to be higher in arterial group when compared with venous group (62.3±24.6mins, 92.7±31.7mins vs 55.9±35.7, 87.8±35.9) respectively due to technically demanding anastomosis with arterial grafts.…”
Section: Discussionmentioning
confidence: 99%
“…5 Because arterial grafts are less likely to develop atherosclerosis and occlusion than venous grafts, arterial grafts may offer greater long-term patency. 3,6 Other arterial grafts that have been used in CABG surgery over time include the Right Internal Mammary Artery (RIMA), the Radial Artery (RA) and the gastroepiploic artery. 6 RA as a bypass conduit in CABG surgery was used by Carpentier and associates in 1973 who reported the short-term outcomes of 40 grafts in 30 patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation